2020
DOI: 10.3390/w12041003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Redundancy in Stormwater Structures Under Hydraulic Design

Abstract: As environmental change is happening at an unprecedented pace, a reliable and proper urban drainage design is required to alleviate the negative effects of unexpected extreme rainfall events occurring due to the natural and anthropogenic variations such as climate change and urbanization. Since structure/configuration of a stormwater network plays an imperative role in the design and hydraulic behavior of the system, the goal of this paper is to elaborate upon the significance of possessing redundancy (e.g., a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…In fact, the presence of additional flow paths can provide a better distribution of stormwater, ensuring a continuous drainage of wastewater. Lee et al [33] suggested that networks with higher drainage density, i.e., with a more meshed layout, are inducing lower runoff peaks than branched systems. Based on this, the reduction of the annual number of CSO events might be explained by the fact that lower peaks in higher meshness networks implies lower water levels in the pipes, hence the threshold depth for activation of CSOs is then not so frequently exceeded.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the presence of additional flow paths can provide a better distribution of stormwater, ensuring a continuous drainage of wastewater. Lee et al [33] suggested that networks with higher drainage density, i.e., with a more meshed layout, are inducing lower runoff peaks than branched systems. Based on this, the reduction of the annual number of CSO events might be explained by the fact that lower peaks in higher meshness networks implies lower water levels in the pipes, hence the threshold depth for activation of CSOs is then not so frequently exceeded.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is a strong need for adaptation of water infrastructure to tackle challenges like climate change, increasing urbanization, etc. [4]. It requires resilience evaluation and intervention planning, in which the former is to develop a comprehensive understanding of the inherent resilience of the entire underlying system, and the latter is to provide evidence-based strategies for optimizing water infrastructure resilience at the lowest possible cost within its life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Structural decentralization strategies reduce the degree of centralization (DC) by reducing the number of elements that are linked and interconnected by releasing stormwater by various outlets to different water bodies locations (see Section 2.2) [10]. Structural resilience is often neglected in the design of UDSs [31][32][33]. However, it can play a significant role in system performance during extreme events.…”
Section: Introductionmentioning
confidence: 99%